Structured Intervention Units and Mental Health in Canadian Federal Prisons - Lamiah Adamjee (McMaster University Library Press, 2022)
On 21 June 2019, the federal government passed Bill C-83: An Act to amend the Corrections and Conditional Release Act and another Act with the primary intention of eliminating the use of administrative and disciplinary segregation in Canadian federal prisons and replacing the practice with structured intervention units. This new correctional model would serve as a way to separate unsafe inmates while ensuring they receive appropriate mental health services, increased time outside of their units, and meaningful human contact. The conception of Bill C-83 was largely a result of a history of widespread criticisms that administrative segregation infringed on human rights, posed significant mental health concerns, and violated the Canadian Charter of Rights and Freedoms. While the reform mitigated immediate pressure on the federal government to act, several advocacy groups, legal experts, politicians, and other stakeholders voiced negative opinions and indicated the shortcomings of the new units and the impact they will have on the health of prisoners. Bill C-83 has the potential to prompt significant change in the context of prison health reform, but this will be dependent on the federal government's coordination with Correctional Services Canada. Le gouvernement fédéral a fait adopter le 21 juin 2019 le projet de loi C-83 : transformer le système correctionnel afin de mettre l'accent sur la réinsertion sociale et les soins de santé mental, dont l'intention première était de supprimer le recours à l'isolement administratif disciplinaire dans les prisons fédérales canadiennes et de le remplacer par des unités d'intervention structurées. Ce nouveau modèle correctionnel vise à séparer les prisonniers dangereux tout en garantissant qu'ils reçoivent les soins de santé mentale nécessaires, qu'ils aient du temps hors de leurs unités et des contacts humains significatifs. Le projet de loi C-83 a été conçu largement en réponse à une série de critiques tenant que l'isolement administratif bafouait des droits élémentaires, présentait des risques importants pour la santé mentale et violait la Charte canadienne des droits et libertés. Parce que la réforme atténuait le besoin d'action immédiate de la part du gouvernement fédéral, plusieurs groupes de défense, des experts juridiques, des politiques et autres acteurs ont exprimé leur opposition et souligné les défauts des nouvelles unités ainsi que l'impact qu'elles auront sur la santé des prisonniers. Le projet de loi C-83 peut apporter un changement significatif dans le contexte de la réforme de la santé en prison, mais ceci dépendra du degré de coordination entre le gouvernement fédéral et Service correctionnel Canada.